Decontamination in the Electron Probe Microanalysis with a Peltier-Cooled Cold Finger. (5th October 2016) - Buse, Ben; Kearns, Stuart; Clapham, Charles; Hawley, Donovan
Abstract: A prototype Peltier thermoelectric cooling unit has been constructed to cool a cold finger on an electron microprobe. The Peltier unit was tested at 15 and 96 W, achieving cold finger temperatures of −10 and −27°C, respectively. The Peltier unit did not adversely affect the analytical stability of the instrument. Heat conduction between the Peltier unit mounted outside the vacuum and the cold finger was found to be very efficient. Under Peltier cooling, the vacuum improvement associated with water vapor deposition was not achieved; this has the advantage of avoiding severe degradation of the vacuum observed when warming up a cold finger from liquid nitrogen (LN2 ) temperatures. Carbon contamination rates were reduced as cooling commenced; by −27°C contamination rates were found to be comparable with LN2 -cooled devices. Peltier cooling, therefore, provides a viable alternative to LN2 -cooled cold fingers, with few of their associated disadvantages.